MODEL MANAJEMEN E-LEARNING DI PERGURUAN TINGGI - Lantip Diat Prasojo (MAJALAH ILMIAH PEMBELAJARAN, 2009)
Information and Communication Technology (ICT) is growing fast included in the case of learning management based on ICT. Learning management based on ICT which is being trend namely e-learning management. E-learning management has implemented to educational institutions. Based on the background, thus emerged general problem ”how e-learning management at university can increase quality college students’ learning outcome quality”.The effectiveness and efficiency of E-learning management at university can be measured from some steps as follows: 1) Policy in conducting e-learning system, 2) University Lecturers’ understanding on e-learning technology, 3) College student’s understanding on e-learning technology, 4) University lecturer’s readiness toward learning process by using e-learning system, 5) University college students’ readiness toward learning process by using e-learning system, 6) infrastructure readiness of e-learning system such as consist of: hardware (LAN dan WAN), software, brainware, 7) the system of human resources counseling supporting e-learning system, 8) funding of e-learning system, 9) learning process by using e-learning system at university, 10) controlling system toward the learning process by using e-learning system at university, 11) the impact of learning process by e-learning toward the increasing of college students’ learning outcome quality.